An Effect of Individual Characteristics and Work Environment on Employee Motivation and Performance - Prasetyo Rizky Putra; Rindi Andika; Hasrul Azwar Hasibuan (Budapest International Research and Critics University, 2022)
The role of HR is increasing is important when viewed from the supply and demand side of the labor market, where human capital is the level of compatibility between demand and supply of labor with the quality and quantity of HR itself. Therefore, this study aims to determine the effect of individual characteristics and work environment on employee motivation and performance, and to determine the effect of employee motivation intervening on individual characteristics and work environment on performance. This study uses quantitative methods with the aim of testing hypotheses with the object of this research being all employees of PT. Merapi Utama Pharma Medan Branch, which is located at Jalan Tapian Nauli Pasar 1 No. 5 districts. Sunggal, Kel. Medan Sunggal, Medan 20138 with 76 employees consisting of marketing staff and administrative staff. This company is engaged in pharmaceutical wholesalers whose products are in the form of services in the distribution of medical devices, medicines, infusion fluids and equipment, as well as health food. PT. Merapi Utama Pharma distributes goods from the company or commonly called Principal to hospitals, pharmacies, outlets, supermarkets and mini markets. The data collection technique used a census because the total population was only 76 people. Hypothesis testing using path analysis. The results showed that individual characteristics had a significant effect on employee motivation and performance, the work environment had a significant effect on employee motivation but had no significant effect on performance. The test results show that employee motivation variables mediate the effect of individual characteristics and work environment on performance. This study updates the motivation variable as an intervening variable between individual characteristics variables, performance variables, research locations, and variable relationship models. The limitations of this study include the number of samples which are only 76 subjectivities. In addition, the re-examination should be conducted again in a different place with a larger sample.